ANALISIS INTEGRASI PASAR BAWANG MERAH DI KABUPATEN PAMEKASAN - Sumaiyah, Siti; Subari, Slamet; M.Ariyani, Aminah Happy (Agriekonomika, 2013)
ABSTRACTThe experiment was conducted in the village of Lesong Daya, Batumarmar District and Sub Market Waru Pamekasan. The purpose of this study is to know the marketing channels and marketing margins of onions in the village of Lesong Daya Batumarmar District and know the market integration at the level of onion farmers in the village and at the level of traders in the Waru Market, Lesong Daya Batumarmar Pamekasan. The sampling method in this research used Snowball Sampling. While the analysis method used were the marketing margin and market integration analysis. The results showed that there are two marketing channels onion in the Village of Lesong Daya, Batumarmar District and based on analysis of marketing margins, farmers share, as well as the distribution margin shows that when farmers sell onion in dry conditions on marketing channel pattern I is more efficient than other marketing channel. Based on the analysis of price, strong integrated market in both the short term and long term based on the integration of the average monthly price of onion from January 2012 to April 2013.Keywords: Marketing Channels, Marketing Margins, Market Integration